Pulmonary embolism complicated with necrotic debris in the lung parenchyma, treated by right lower lobectomy: a case report - Hikaru Watanabe; Naoki Kanauchi (Surgical Case Reports, 2019)
Abstract Background It is uncommon for aseptic necrosis to occur in the lung parenchyma as a result of acute pulmonary embolism, because of the dual blood supply of the lung. We report a case in which acute pulmonary embolism led to pulmonary infarction and progressive lung necrosis, requiring treatment with right lower lobe resection. Case presentation A 63-year-old man was referred to our hospital for right-side pleuritic chest pain and fever. He was then admitted in another department in our hospital with a diagnosis of pneumonia. Antimicrobial therapy was initiated; however, laboratory testing elevated white blood cell counts and C-reactive protein. Chest computed tomography revealed acute pulmonary emboli within the right lower lobe segmental pulmonary arteries, as well as a small cavity lesion within the same lobe, which measured 1.2 cm in diameter. Treatment strategies included anticoagulation therapy, thoracic drainage of the affected side, and an antibiotic escalation protocol. However, the patient’s fever did not subside; additionally, his leukocyte count increased after 3 days of the new treatment protocol. We considered it to be difficult to achieve cure with medical treatment alone; therefore, we performed a right lower lobectomy. Conclusions We report an unusual case in which inflammation arose from lung necrosis secondary to lung embolism, which was not alleviated by conservative treatment; however, it was cured by right lower lobectomy.